Triboelectricity nano-generator and preparation method and application thereof
By introducing a charge storage layer between the friction layer and the electrode layer of the triboelectric nanogenerator and preparing the nanofiber membrane by electrospinning, the problem of insufficient output performance of the existing triboelectric nanogenerator is solved, and higher charge density and output performance are achieved.
Patent Information
- Application Number
- CN202411965020.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
The existing triboelectric nanogenerators have limited their practical applications in some fields due to their small triboelectric current and output power.
By introducing a charge storage layer between the friction layer and the electrode layer, nanofiber membranes are prepared by electrospinning to improve charge storage performance and output performance.
The charge density and output performance of triboelectric nanogenerators are improved, and the charge retention ability and surface charge density are enhanced.
Smart Images

Figure CN119891802A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nano energy technology, and in particular to a triboelectric nanogenerator and a preparation method and application thereof. Background Art
[0002] The continuous development of the times and technology has promoted the rapid progress of wearable electronic devices and sensors, making renewable and clean energy an important power demand of modern society. Triboelectric nanogenerators (TENGs) can effectively convert a variety of weak low-frequency mechanical energy into electrical energy, such as human physiological activities, low-frequency vibrations, wind energy, sound waves, and water energy. Since the triboelectric effect can be realized in almost any material, the material sources for making TENGs are very rich, including paper, fabrics, plastics, and metals. Therefore, triboelectric nanogenerators can serve as an excellent alternative power source for microelectronic devices, effectively solving the current power supply problem of microelectronic devices, and showing broad application prospects in the fields of wearable devices, flexible sensors, and energy harvesting.
[0003] However, the triboelectric current and output power of general TENG are usually small, which limits its practical application in some fields. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a triboelectric nanogenerator and its preparation method and application, which can store charges to a higher degree, avoid the neutralization of negative charges and positive charges induced by the electrodes to improve the charge retention capacity of the friction layer, effectively improve the contact area of the film, provide more adsorption sites for the charges, give it better charge storage performance, increase the charge density, and further improve the output performance of the triboelectric nanogenerator.
[0005] To achieve the above object, the present invention is implemented by adopting the following technical solutions:
[0006] In a first aspect, the present invention provides a triboelectric nanogenerator, comprising an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0007] The charge storage layer is a nanofiber film containing polymer fibers, and the polymer is selected from one or more of polyimide, polyvinylidene fluoride, polydimethylsiloxane, polystyrene, polyethylene terephthalate and nylon.
[0008] Furthermore, the thickness of the charge storage layer is 32 μm-98 μm;
[0009] And / or, the friction layer has a thickness of 25 μm-50 μm.
[0010] In a second aspect, the present invention provides a method for preparing a triboelectric nanogenerator, comprising:
[0011] The polymer solution is prepared into a nanofiber membrane by electrospinning and collected on the electrode layer to obtain an electrode layer-charge storage layer assembly;
[0012] Laminating the electrode layer-charge storage layer assembly to the friction layer to obtain a triboelectric nanogenerator;
[0013] Among them, if a polyimide nanofiber membrane is prepared, before the electrode layer-charge storage layer assembly is attached to the friction layer, the electrode layer-charge storage layer assembly needs to be placed in a tubular furnace for a thermal imidization reaction.
[0014] Furthermore, when the nanofiber membrane is a polyimide nanofiber membrane, the preparation method of the polymer solution includes: completely dissolving 4,4'-aminodiphenylamine (ODA) in a solvent A, and then adding pyromellitic dianhydride to carry out a polymerization reaction to obtain a polyamic acid polymer solution, wherein the solvent A is selected from dimethylformamide or dimethylacetamide;
[0015] When the nanofiber membrane is a polyvinylidene fluoride nanofiber membrane, the preparation method of the polymer solution comprises: adding polyvinylidene fluoride to solvent B, heating to 45-65° C. and stirring until the polyvinylidene fluoride is completely dissolved in solvent B, to obtain a polyvinylidene fluoride polymer solution, wherein the solvent B is selected from dimethylformamide, acetone or dimethyl sulfoxide;
[0016] When the nanofiber membrane is a polydimethylsiloxane nanofiber membrane, the preparation method of the polymer solution comprises: completely dissolving polydimethylsiloxane in a solvent C, adding a cross-linking agent, and stirring until the polydimethylsiloxane is completely dissolved in the solvent C to obtain a polydimethylsiloxane polymer solution, wherein the solvent C is selected from dimethylformamide, tetrahydrofuran or ethyl acetate, the cross-linking agent is tetraethyl orthosilicate, and the mass ratio of the cross-linking agent to the polydimethylsiloxane is 1:10;
[0017] When the nanofiber membrane is a polystyrene nanofiber membrane, the method for preparing the polymer solution comprises: completely dissolving polystyrene in a solvent D to obtain a polystyrene polymer solution, wherein the solvent D is selected from dimethylformamide or tetrahydrofuran;
[0018] When the nanofiber membrane is a polyethylene terephthalate nanofiber membrane, the preparation method of the polymer solution comprises: adding polyethylene terephthalate to a solvent E, heating to 48-68° C. and stirring until the polyethylene terephthalate is completely dissolved in the solvent E, to obtain a polyethylene terephthalate polymer solution, wherein the solvent E is selected from hexafluoroisopropanol, trifluoroacetic acid or chloroform;
[0019] When the nanofiber membrane is a nylon nanofiber membrane, the method for preparing the polymer solution comprises: completely dissolving nylon in a solvent F to obtain a nylon polymer solution, wherein the solvent F is selected from dimethylformamide, dichloromethane, formic acid or dimethyl sulfoxide.
[0020] Furthermore, the polymer has a dielectric constant greater than 1.8 and is polar;
[0021] and / or, the concentration of the polymer solution is 14wt%-18wt%;
[0022] Furthermore, the electrospinning speed is 0.72-1.44 mL / h, the voltage is 16-25 kV, and the receiving distance is 15.5-20.5 cm.
[0023] Furthermore, the electrode layer-charge storage layer assembly is placed in a tube furnace for thermal imidization reaction, the reaction temperature is 250-350° C., and the tube furnace is heated in a gradient heating manner.
[0024] Furthermore, after laminating the electrode layer-charge storage layer assembly to the friction layer, a wire needs to be connected to the electrode layer to obtain a triboelectric nanogenerator.
[0025] In a third aspect, the present invention provides an application of a triboelectric nanogenerator in energy harvesting and self-powered sensors.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The triboelectric nanogenerator provided by the present invention and its preparation method and application introduce a new transition layer, namely, a charge storage layer, between the friction layer and the electrode layer. Since the nanofibers have a small diameter and a large specific surface area, and the surface structure has an interfacial effect of interlaced fibers, when the nanofibers are interlaced or interwoven with each other, the contact surfaces between the fibers may form new interfaces and trap sites, and the trap sites can trap the charges in deep traps in the dielectric layer and make it difficult to escape, and can store charges to a higher degree, avoiding the neutralization of negative charges with positive charges induced by the electrodes to improve the charge retention capacity of the friction layer, and further improving the output performance of the triboelectric nanogenerator;
[0028] The triboelectric nanogenerator and its preparation method and application provided by the present invention have a high specific surface area and porosity when preparing the nanofiber membrane by electrospinning. The porous structure can increase the surface roughness of the nanofiber membrane, effectively improve the contact area of the film, provide more adsorption sites for charges, give it better charge storage performance, and increase the charge density, thereby achieving the purpose of improving the output performance of the triboelectric nanogenerator;
[0029] The triboelectric nanogenerator provided by the present invention and its preparation method and application adopt a method of directly using the electrode layer material as collecting paper to receive fiber spinning to obtain a double-layer component with an electrode layer and a charge storage layer, which simplifies the preparation process of the triboelectric nanogenerator, improves the preparation efficiency and the adhesion between the charge storage layer and the electrode layer, and to a certain extent makes the performance output of the prepared charge storage layer-triboelectric nanogenerator more stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A flow chart of the preparation of a triboelectric nanogenerator provided in an embodiment of the present invention;
[0031] Figure 2 A working principle diagram of the triboelectric nanogenerator provided in embodiments 1, 2, 11 and 12 of the present invention;
[0032] Figure 3 Fiber microstructure diagram of the nanofiber membranes prepared in Examples 2, 3, 4 of the present invention and Comparative Examples 1 and 2;
[0033] Figure 4 Fiber diameter distribution diagram of the nanofiber membranes prepared in Examples 2, 3, 4 of the present invention and Comparative Examples 1 and 2;
[0034] Figure 5 The open circuit voltage, short circuit current and transfer charge diagram of the triboelectric nanogenerators prepared in Examples 2, 3, 4 of the present invention and Comparative Examples 1 and 2;
[0035] Figure 6 Fiber microstructure diagram of the nanofiber membranes prepared in Examples 2, 5, 6 of the present invention and Comparative Examples 3 and 4;
[0036] Figure 7 Fiber diameter distribution diagram of the nanofiber membranes prepared in Examples 2, 5, 6 of the present invention and Comparative Examples 3 and 4;
[0037] Figure 8 The open circuit voltage, short circuit current and transfer charge diagram of the triboelectric nanogenerators prepared in Examples 2, 5, 6 of the present invention and Comparative Examples 3 and 4;
[0038] Fig. 9 The open circuit voltage, short circuit current and transfer charge diagram of the triboelectric nanogenerators prepared in Examples 2, 7, 8 of the present invention and Comparative Examples 5 and 6;
[0039] Fig.10 The open circuit voltage, short circuit current and transfer charge diagram of the triboelectric nanogenerators prepared in Examples 2, 9, 10 of the present invention and Comparative Examples 7 and 8;
[0040] Fig.11The open circuit voltage, short circuit current and transfer charge diagram of the triboelectric nanogenerator prepared in Example 2 of the present invention and Comparative Example 9.
[0041] In the figure: 1. polymer; 2. polymer solution; 3. electrospinning equipment; 4. nanofiber membrane; 5. substrate; 6. electrode layer; 7. charge storage layer; 8. friction layer. DETAILED DESCRIPTION
[0042] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0043] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.
[0044] In the present invention, unless otherwise specified, the raw material information involved in the embodiments of the present invention is as follows: 4,4'-aminodiphenylamine (ODA) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; pyromellitic dianhydride (PMDA) was purchased from TCI (Shanghai) Chemical Industry Development Co., Ltd.; dimethylformamide (DMF) was purchased from Taicang Hushi Reagent Co., Ltd.; polyvinylidene fluoride (PVDF) was purchased from Shanghai Dibai Biotechnology Co., Ltd.; polydimethylsiloxane (PDMS) was purchased from Beijing Inokai Technology Co., Ltd.; tetrahydrofuran (THF) was purchased from Sinopharm Chemical Reagent Suzhou Co., Ltd.; polystyrene (PS) was purchased from Shanghai Bailingwei Chemical Technology Co., Ltd.; acetone was purchased from Jiangsu Qiangsheng Functional Chemical Co., Ltd.; polyethylene terephthalate (PET) was purchased from Hangzhou Fude Biotechnology Co., Ltd.; hexafluoro Isopropyl alcohol (HFIP) was purchased from Sinopharm Chemical Reagent Suzhou Co., Ltd.; nylon (NY) was purchased from Shanghai Titan Technology Co., Ltd.; formic acid was purchased from Shanghai Bailingwei Chemical Technology Co., Ltd.; dichloromethane (DCM) was purchased from Sinopharm Chemical Reagent Suzhou Co., Ltd.; high-purity oxygen-free copper foil (Cu) was purchased from Hefei Wenghe Metal Materials Co., Ltd.; polytetrafluoroethylene (PTFE) was purchased from Shanghai Daoguan Rubber & Plastic Hardware Co., Ltd.; polyvinyl alcohol (PVA) was purchased from Guangzhou Yiyin Water Consumables Wholesale Co., Ltd.; transparent acrylic substrate was purchased from Wenzhou Tang Minji Building Materials Co., Ltd.; Kapton® commercial polyimide film was purchased from Zhongshan Chenxi Technology Co., Ltd.; commercial polyvinylidene fluoride film was purchased from the official website of White Shark Biotechnology Co., Ltd.; conductive glue was purchased from China Scientific Microscope Consumables Co., Ltd.; and wires were purchased from Yueqing Youning Electric Co., Ltd.
[0045] In the present invention, unless otherwise specified, the open circuit voltage, short circuit current and transfer charge tested in the embodiments of the present invention are measured using a graphic sampling multimeter, model DMM7510, purchased from KEITHLEY; a high resistance / low current electrometer, model 6514, purchased from KEITHLEY; and a triboelectric performance test platform, which is built in the laboratory.
[0046] In the present invention, unless otherwise specified, the film thickness tested in the examples of the present invention is measured using a digital micrometer, model 0-25, purchased from SYNTEK.
[0047] Example 1
[0048] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0049] In this embodiment, the charge storage layer is made of polyvinylidene fluoride nanofiber film.
[0050] The preparation method of the triboelectric nanogenerator is as follows Figure 1 As shown, first, the polymer 1 is prepared into a polymer solution 2, and the polymer solution 2 is prepared into a nanofiber membrane 4 using an electrospinning device 3 as a charge storage layer 7, and collected on an electrode layer 6 to obtain an electrode layer-charge storage layer assembly, and the electrode layer-charge storage layer assembly is bonded to a friction layer 8 on a substrate 5 to obtain a friction electric nanogenerator.
[0051] The preparation method of the triboelectric nanogenerator provided in this embodiment includes:
[0052] S1. Preparation of spinning solution: 2.8 g of polyvinylidene fluoride (PVDF) powder was weighed and added into a 50 ml beaker, and then 6.88 g of dimethylformamide (DMF) and 10.32 g of acetone (DMF to acetone mass ratio 2:3) were added respectively, and heated in a water bath at 60°C for 2 h to obtain a PVDF spinning solution with a mass fraction of 14 wt%;
[0053] S2. Preparation of charge storage layer-nanofiber membrane: PVDF spinning solution was loaded into the electrospinning equipment, and the electrospinning process parameters were set as spinning voltage 18 kV, receiving distance 16 cm, micro pump pushing speed 1.0 mL / h, and receiving device speed 300 r / min, and electrospinning was performed to deposit the nanofibers onto the high-purity oxygen-free copper foil (thickness 50 μm) of the collecting drum, and the spinning time was controlled to obtain a PVDF nanofiber membrane with a thickness of 50 μm, and the PVDF nanofiber membrane was cut into a size of 6 cm×6 cm to obtain an electrode layer (Cu)-charge storage layer (PVDF) assembly;
[0054] S3. Preparation of TENG: Use conductive glue to stick the electrode layer (Cu)-charge storage layer (PVDF) assembly on the transparent acrylic substrate, and connect the wire between the substrate and the copper electrode; select a PTFE film with a thickness of 25μm and cut it into a size of 6cm×6cm as a friction layer, and then use conductive glue to stick the PTFE film to one side of the nanofiber membrane to prepare TENG.
[0055] Example 2
[0056] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0057] In this embodiment, the charge storage layer is made of polyimide nanofiber film.
[0058] Reference Figure 1 As shown, the preparation method of the triboelectric nanogenerator includes:
[0059] S1. Preparation of spinning solution: 4 g of 4,4'-aminodiphenylamine (ODA) was added to 43.89 g of dimethylformamide, and the mixture was fully stirred at 25°C. Then, 4.36 g of pyromellitic anhydride (PMDA) was added to the solution four times (the molar ratio of ODA to PMDA was 1:1.02). Except for the last time, the amount of ODA added each time was 1 / 2 of the remaining amount (2.18 g, 1.09 g, 0.55 g, 0.54 g). The mixture was fully stirred and reacted for 6.5 h to polymerize into a polyamic acid (PAA) spinning solution with a mass fraction of 16 wt%;
[0060] S2. Preparation of charge storage layer-nanofiber membrane: The PAA spinning solution was loaded into the electrospinning equipment, and the electrospinning process parameters were set as spinning voltage 20 kV, receiving distance 18 cm, micro pump push speed 1.08 mL / h, and receiving device speed 200 r / min, and electrospinning was performed to deposit the nanofibers onto the high-purity oxygen-free copper foil (50 μm) of the collecting drum, and the spinning time was controlled to obtain a PAA nanofiber membrane with a thickness of 34 μm; the PAA nanofiber membrane was cut into a size of 6 cm×6 cm and placed in a tubular furnace and protected by nitrogen, and then subjected to gradient heating: 40 min to 80°C for 1 h; 40 min from 80°C to 160°C for 1 h; 45 min from 160°C to 250°C for 1 h; 50 min from 250°C to 350°C for 0.5 h; it was thermally imidized under high temperature conditions to form a PI nanofiber membrane to obtain an electrode layer (Cu)-charge storage layer (PI) component;
[0061] S3. Preparation of TENG: Use conductive glue to stick the electrode layer (Cu)-charge storage layer (PI) assembly on a transparent acrylic substrate, and connect the wire between the substrate and the copper electrode; select a PTFE film with a thickness of 25μm and cut it into a size of 6cm×6cm as a friction layer, and then use conductive glue to stick the PTFE film to one side of the nanofiber membrane to prepare TENG.
[0062] Example 3
[0063] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0064] In this embodiment, the charge storage layer is made of polyimide nanofiber film.
[0065] Different from Example 2, in this example, the method for preparing the triboelectric nanogenerator includes step S1 as follows:
[0066] S1. Preparation of spinning solution: 4 g of 4,4'-aminodiphenylamine (ODA) was added to 51.354 g of dimethylformamide, and the mixture was stirred thoroughly at 25°C. Then, 4.36 g of pyromellitic anhydride (PMDA) was added to the solution four times (the molar ratio of ODA to PMDA was 1:1.02). Except for the last time, the amount of ODA added each time was 1 / 2 of the remaining amount (2.18 g, 1.09 g, 0.55 g, 0.54 g). The mixture was stirred thoroughly and reacted for 6.5 h to polymerize into a PAA spinning solution with a mass fraction of 14 wt%;
[0067] The remaining steps and parameters are the same as those in Example 2.
[0068] Example 4
[0069] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0070] In this embodiment, the charge storage layer is made of polyimide nanofiber film.
[0071] Different from Example 2, in this example, the method for preparing the triboelectric nanogenerator includes step S1 as follows:
[0072] S1. Preparation of spinning solution: 4 g of 4,4'-aminodiphenylamine (ODA) was added to 38.10 g of dimethylformamide, and the mixture was fully stirred at 25°C. Then, 4.36 g of pyromellitic anhydride (PMDA) was added to the solution four times (the molar ratio of ODA to PMDA was 1:1.02). Except for the last time, the amount of ODA added each time was 1 / 2 of the remaining amount (2.18 g, 1.09 g, 0.55 g, 0.54 g). The mixture was fully stirred and reacted for 6.5 h to polymerize into a PAA spinning solution with a mass fraction of 18 wt%;
[0073] The remaining steps and parameters are the same as those in Example 2.
[0074] Example 5
[0075] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0076] In this embodiment, the charge storage layer is made of polyimide nanofiber film.
[0077] Different from Example 2, in this embodiment, the method for preparing the triboelectric nanogenerator includes step S2 as follows:
[0078] S2. Preparation of charge storage layer-nanofiber membrane: load the PAA spinning solution into the electrospinning equipment, set the electrospinning process parameters as spinning voltage 17kV, receiving distance 18cm, micro pump push speed 1.08mL / h, receiving device speed 200r / min, perform electrospinning, deposit the nanofibers on the high-purity oxygen-free copper foil (50μm) of the collecting drum, control the spinning time to obtain a PAA nanofiber membrane with a thickness of 34μm; cut the PAA nanofiber membrane to a size of 6cm×6cm and put it into a tubular furnace and pass nitrogen for protection, and then heat it gradually: 40min to 80℃ for 1h; continue to heat from 80℃ to 160℃ for 40min for 1h; continue to heat from 160℃ to 250℃ for 45min for 1h; continue to heat from 250℃ to 350℃ for 50min for 0.5h; thermal imidization is performed under high temperature conditions to form a PI nanofiber membrane to obtain an electrode layer (Cu)-charge storage layer (PI) component;
[0079] The remaining steps and parameters are the same as those in Example 2.
[0080] Example 6
[0081] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0082] In this embodiment, the charge storage layer is made of polyimide nanofiber film.
[0083] Different from Example 2, in this embodiment, the method for preparing the triboelectric nanogenerator includes step S2 as follows:
[0084] The PAA spinning solution was loaded into the electrospinning equipment, and the electrospinning process parameters were set as spinning voltage 23 kV, receiving distance 18 cm, micro pump push speed 1.08 mL / h, and receiving device speed 200 r / min, and electrospinning was performed to deposit the nanofibers on the high-purity oxygen-free copper foil (50 μm) of the collecting drum, and the spinning time was controlled to obtain a PAA nanofiber membrane with a thickness of 34 μm; the PAA nanofiber membrane was cut into a size of 6 cm×6 cm and placed in a tubular furnace and protected by nitrogen, and subjected to gradient heating: 40 min to 80°C for 1 h; 40 min from 80°C to 160°C for 1 h; 45 min from 160°C to 250°C for 1 h; 50 min from 250°C to 350°C for 0.5 h; it was thermally imidized under high temperature conditions to form a PI nanofiber membrane to obtain an electrode layer (Cu)-charge storage layer (PI) component;
[0085] The remaining steps and parameters are the same as those in Example 2.
[0086] Example 7
[0087] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0088] In this embodiment, the charge storage layer is made of polyimide nanofiber film.
[0089] Different from Example 2, in this embodiment, the method for preparing the triboelectric nanogenerator includes step S2 as follows:
[0090] The PAA spinning solution was loaded into the electrospinning equipment, and the electrospinning process parameters were set as spinning voltage 20 kV, receiving distance 18 cm, micro pump push speed 0.72 mL / h, and receiving device speed 200 r / min, and electrospinning was performed to deposit the nanofibers on the high-purity oxygen-free copper foil (50 μm) of the collecting drum. The spinning time was controlled to obtain a PAA nanofiber membrane with a thickness of 34 μm. The PAA nanofiber membrane was cut into a size of 6 cm×6 cm and placed in a tubular furnace and protected by nitrogen. The temperature was gradually increased: 40 min to 80°C for 1 h; 40 min from 80°C to 160°C for 1 h; 45 min from 160°C to 250°C for 1 h; 50 min from 250°C to 350°C for 0.5 h; it was thermally imidized into a PI nanofiber membrane under high temperature conditions to obtain an electrode layer (Cu)-charge storage layer (PI) component;
[0091] The remaining steps and parameters are the same as those in Example 2.
[0092] Example 8
[0093] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0094] In this embodiment, the charge storage layer is made of polyimide nanofiber film.
[0095] Different from Example 2, in this embodiment, the method for preparing the triboelectric nanogenerator includes step S2 as follows:
[0096] The PAA spinning solution was loaded into the electrospinning equipment, and the electrospinning process parameters were set as spinning voltage 20 kV, receiving distance 18 cm, micro pump push speed 1.44 mL / h, and receiving device speed 200 r / min, and electrospinning was performed to deposit the nanofibers on the high-purity oxygen-free copper foil (50 μm) of the collecting drum, and the spinning time was controlled to obtain a PAA nanofiber membrane with a thickness of 76 μm; the PAA nanofiber membrane was cut into a size of 6 cm×6 cm and placed in a tubular furnace and protected by nitrogen, and subjected to gradient heating: 40 min to 80°C for 1 h; 40 min from 80°C to 160°C for 1 h; 45 min from 160°C to 250°C for 1 h; 50 min from 250°C to 350°C for 0.5 h; it was thermally imidized under high temperature conditions to form a PI nanofiber membrane to obtain an electrode layer (Cu)-charge storage layer (PI) component;
[0097] The remaining steps and parameters are the same as those in Example 2.
[0098] Example 9
[0099] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0100] In this embodiment, the charge storage layer is made of polyimide nanofiber film.
[0101] Different from Example 2, in this embodiment, the method for preparing the triboelectric nanogenerator includes step S2 as follows:
[0102] The PAA spinning solution was loaded into the electrospinning equipment, and the electrospinning process parameters were set as spinning voltage 20 kV, receiving distance 18 cm, micro pump push speed 1.08 mL / h, and receiving device speed 200 r / min, and electrospinning was performed to deposit the nanofibers on the high-purity oxygen-free copper foil (50 μm) of the collecting drum, and the spinning time was controlled to obtain a PAA nanofiber membrane with a thickness of 49 μm; the PAA nanofiber membrane was cut into a size of 6 cm×6 cm and placed in a tubular furnace and protected by nitrogen, and subjected to gradient heating: 40 min to 80°C for 1 h; 40 min from 80°C to 160°C for 1 h; 45 min from 160°C to 250°C for 1 h; 50 min from 250°C to 350°C for 0.5 h; it was thermally imidized under high temperature conditions to form a PI nanofiber membrane to obtain an electrode layer (Cu)-charge storage layer (PI) component;
[0103] The remaining steps and parameters are the same as those in Example 2.
[0104] Example 10
[0105] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0106] In this embodiment, the charge storage layer is made of polyimide nanofiber film.
[0107] Different from Example 2, in this embodiment, the method for preparing the triboelectric nanogenerator includes step S2 as follows:
[0108] The PAA spinning solution was loaded into the electrospinning equipment, and the electrospinning process parameters were set as spinning voltage 20 kV, receiving distance 18 cm, micro pump push speed 1.08 mL / h, and receiving device speed 200 r / min, and electrospinning was performed to deposit the nanofibers on the high-purity oxygen-free copper foil (50 μm) of the collecting drum, and the spinning time was controlled to obtain PAA nanofibers with a thickness of 76 μm; the PAA nanofiber membrane was cut into a size of 6 cm×6 cm and placed in a tubular furnace and protected by nitrogen, and subjected to gradient heating: 40 min to 80°C for 1 h; 40 min from 80°C to 160°C for 1 h; 45 min from 160°C to 250°C for 1 h; 50 min from 250°C to 350°C for 0.5 h; it was thermally imidized under high temperature conditions to form a PI nanofiber membrane to obtain an electrode layer (Cu)-charge storage layer (PI) component;
[0109] The remaining steps and parameters are the same as those in Example 2.
[0110] Embodiment 11
[0111] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0112] In this embodiment, the charge storage layer is made of polydimethylsiloxane nanofiber membrane.
[0113] The preparation method of the triboelectric nanogenerator is as follows Figure 1 As shown, first, the polymer 1 is prepared into a polymer solution 2, and the polymer solution 2 is prepared into a nanofiber membrane 4 using an electrospinning device 3 as a charge storage layer 7, and collected on an electrode layer 6 to obtain an electrode layer-charge storage layer assembly, and the electrode layer-charge storage layer assembly is bonded to a friction layer 8 on a substrate 5 to obtain a friction electric nanogenerator.
[0114] The preparation method of the triboelectric nanogenerator provided in this embodiment includes:
[0115] S1. Preparation of spinning solution: 3.6 g of polydimethylsiloxane (PDMS) polymer powder was weighed and added into a 50 ml beaker, and then 12.3 g of dimethylformamide (DMF) and 4.1 g of tetrahydrofuran (THF) (the mass ratio of DMF to THF was 3:1) were added respectively, and then a cross-linking agent, tetraethyl orthosilicate (TEOS) (the mass ratio of PDMS to TEOS was 10:1) was added and stirred at room temperature for 12 h to obtain a PDMS spinning solution with a mass fraction of 18 wt%;
[0116] S2. Preparation of charge storage layer-nanofiber membrane: load the PDMS spinning solution into the electrospinning equipment, set the electrospinning process parameters as spinning voltage 19 kV, receiving distance 17 cm, micro pump push speed 1.21 mL / h, receiving device speed 300 r / min, perform electrospinning, deposit the nanofibers onto the high-purity oxygen-free copper foil (50 μm) of the collecting drum, control the spinning time to obtain a PDMS nanofiber membrane with a thickness of 64 μm, then put it into an oven for drying at 80°C for 2 h, take it out and cut the PDMS nanofiber membrane into a size of 6 cm×6 cm to obtain an electrode layer (Cu)-charge storage layer (PDMS) assembly;
[0117] S3. Preparation of TENG: Use conductive glue to stick the electrode layer (Cu)-charge storage layer (PDMS) assembly on the transparent acrylic substrate, and connect the wire between the substrate and the copper electrode; select a PTFE film with a thickness of 25μm and cut it into a size of 6cm×6cm as a friction layer, and then use conductive glue to stick the PTFE film to one side of the nanofiber membrane to prepare TENG.
[0118] Example 12
[0119] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0120] In this embodiment, the charge storage layer is made of polystyrene nanofiber film.
[0121] The preparation method of the triboelectric nanogenerator is as follows Figure 1 As shown, first, the polymer 1 is prepared into a polymer solution 2, and the polymer solution 2 is prepared into a nanofiber membrane 4 using an electrospinning device 3 as a charge storage layer 7, and collected on an electrode layer 6 to obtain an electrode layer-charge storage layer assembly, and the electrode layer-charge storage layer assembly is bonded to a friction layer 8 on a substrate 5 to obtain a friction electric nanogenerator.
[0122] S1. Preparation of spinning solution: 2.7 g of poly(styrene) (PS) polymer powder was weighed and added into a 50 ml beaker, and then 11.25 g of dimethylformamide (DMF) and 3.75 g of tetrahydrofuran (THF) (DMF to THF mass ratio 3:1) were added respectively, and stirred at 20°C for 12 h to obtain a PS spinning solution with a mass fraction of 18 wt%;
[0123] S2. Preparation of charge storage layer-nanofiber membrane: PS spinning solution was loaded into the electrospinning equipment, and the electrospinning process parameters were set as spinning voltage 20 kV, receiving distance 16 cm, micro pump pushing speed 1.2 mL / h, and receiving device speed 300 r / min, and electrospinning was performed to deposit the nanofibers onto the high-purity oxygen-free copper foil (50 μm) of the collecting drum. The spinning time was controlled to obtain a PS nanofiber membrane with a thickness of 62 μm, and the PS nanofiber membrane was cut into a size of 6 cm×6 cm to obtain an electrode layer (Cu)-charge storage layer (PS) assembly;
[0124] S3. Preparation of TENG: Use conductive glue to stick the electrode layer (Cu)-charge storage layer (PS) assembly on a transparent acrylic substrate, and connect the wire between the substrate and the copper electrode; select a PTFE film with a thickness of 25μm and cut it into a size of 6cm×6cm as a friction layer, and then use conductive glue to stick the PTFE film to one side of the nanofiber membrane to prepare TENG.
[0125] Example 13
[0126] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0127] In this embodiment, the charge storage layer is made of polyethylene terephthalate nanofiber film.
[0128] The preparation method of the triboelectric nanogenerator is as follows Figure 1 As shown, first, the polymer 1 is prepared into a polymer solution 2, and the polymer solution 2 is prepared into a nanofiber membrane 4 using an electrospinning device 3 as a charge storage layer 7, and collected on an electrode layer 6 to obtain an electrode layer-charge storage layer assembly, and the electrode layer-charge storage layer assembly is bonded to a friction layer 8 on a substrate 5 to obtain a friction electric nanogenerator.
[0129] S1. Preparation of spinning solution: 3.75 g of polyethylene terephthalate (PET) polymer powder was weighed into a 50 ml beaker, and then dried in a vacuum drying oven for 45 min. After taking it out, 21.25 g of hexafluoroisopropanol (HFIP) was added, and heated in a water bath at 50° C. for 8.5 h to obtain a PET spinning solution with a mass fraction of 15 wt%;
[0130] S2. Preparation of charge storage layer-nanofiber membrane: PET spinning solution was loaded into the electrospinning equipment, and the electrospinning process parameters were set as spinning voltage 17 kV, receiving distance 20 cm, micro pump push speed 1.15 mL / h, receiving device speed 300 r / min, and electrospinning was performed to deposit the nanofibers onto the high-purity oxygen-free copper foil (50 μm) of the collecting drum. The spinning time was controlled to obtain a PVDF nanofiber membrane with a thickness of 45 μm. The PET nanofiber membrane was cut into a size of 6 cm×6 cm to obtain an electrode layer (Cu)-charge storage layer (PET) assembly;
[0131] S3. Preparation of TENG: Use conductive glue to stick the electrode layer (Cu)-charge storage layer (PET) assembly on the transparent acrylic substrate, and connect the wire between the substrate and the copper electrode; select a PVA film with a thickness of 25μm and cut it into a size of 6cm×6cm as a friction layer, and then use conductive glue to stick the PVA film to one side of the nanofiber membrane to prepare TENG.
[0132] Embodiment 14
[0133] This embodiment provides a triboelectric nanogenerator and a preparation method thereof, wherein the triboelectric nanogenerator comprises an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer;
[0134] In this embodiment, the charge storage layer is made of nylon nanofiber membrane.
[0135] The preparation method of the triboelectric nanogenerator is as follows Figure 1 As shown, first, the polymer 1 is prepared into a polymer solution 2, and the polymer solution 2 is prepared into a nanofiber membrane 4 using an electrospinning device 3 as a charge storage layer 7, and collected on an electrode layer 6 to obtain an electrode layer-charge storage layer assembly, and the electrode layer-charge storage layer assembly is bonded to a friction layer 8 on a substrate 5 to obtain a friction electric nanogenerator.
[0136] S1. Preparation of spinning solution: Weigh 2 g of nylon (NY) polymer particles in a conical flask, then add 4.2 g of dichloromethane (DCM) and 6.3 g of formic acid (DCM to formic acid mass ratio 2:3), respectively, and heat in a water bath at 40°C for 6 h to obtain a NY spinning solution with a mass fraction of 16 wt%;
[0137] S2. Preparation of charge storage layer-nanofiber membrane: NY spinning solution was loaded into the electrospinning equipment, and the electrospinning process parameters were set as spinning voltage 21 kV, receiving distance 18 cm, micro pump push speed 1.36 mL / h, and receiving device speed 250 r / min. Electrospinning was performed to deposit the nanofibers onto the high-purity oxygen-free copper foil (50 μm) on the collecting drum. The spinning time was controlled to obtain a NY nanofiber membrane with a thickness of 39 μm. The PET nanofiber membrane was cut into a size of 6 cm × 6 cm to obtain an electrode layer (Cu)-charge storage layer (NY) assembly.
[0138] S3. Preparation of TENG: Use conductive glue to stick the electrode layer (Cu)-charge storage layer (NY) assembly on the transparent acrylic substrate, and connect the wire between the substrate and the copper electrode; select a PVA film with a thickness of 25μm and cut it into a size of 6cm×6cm as a friction layer, and then use conductive glue to stick the PVA film to one side of the nanofiber membrane to prepare TENG.
[0139] Comparative Example 1
[0140] This comparative example provides a triboelectric nanogenerator and a preparation method thereof. Different from Example 2, in this comparative example, the preparation method of the triboelectric nanogenerator includes step S1 as follows:
[0141] S1. Preparation of spinning solution: 4 g of 4,4'-aminodiphenylamine (ODA) was added to 61.31 g of dimethylformamide, and the mixture was fully stirred at 25°C. Then, 4.36 g of pyromellitic dianhydride (PMDA) was added to the solution four times (the molar ratio of ODA to PMDA was 1:1.02). Except for the last time, the amount of ODA added each time was 1 / 2 of the remaining amount (2.18 g, 1.09 g, 0.55 g, 0.54 g). The mixture was fully stirred and reacted for 6.5 h to polymerize into a PAA spinning solution with a mass fraction of 12 wt%;
[0142] The remaining steps and parameters are the same as those in Example 2.
[0143] Comparative Example 2
[0144] This comparative example provides a triboelectric nanogenerator and a preparation method thereof. Different from Example 2, in this comparative example, the preparation method of the triboelectric nanogenerator includes step S1 as follows:
[0145] S1. Preparation of spinning solution: 4 g of 4,4'-aminodiphenylamine (ODA) was added to 33.44 g of dimethylformamide, and the mixture was stirred thoroughly at 25°C. Then, 4.36 g of pyromellitic anhydride (PMDA) was added to the solution four times (the molar ratio of ODA to PMDA was 1:1.02). Except for the last time, the amount of ODA added each time was 1 / 2 of the remaining amount (2.18 g, 1.09 g, 0.55 g, 0.54 g). The mixture was stirred thoroughly and reacted for 6.5 h to polymerize into a PAA spinning solution with a mass fraction of 20 wt%;
[0146] The remaining steps and parameters are the same as those in Example 2.
[0147] Comparative Example 3
[0148] This comparative example provides a triboelectric nanogenerator and a preparation method thereof. Different from Example 2, in this comparative example, the preparation method of the triboelectric nanogenerator includes step S2 as follows:
[0149] S2. Preparation of charge storage layer-nanofiber membrane: load the PAA spinning solution into the electrospinning equipment, set the electrospinning process parameters as spinning voltage 14kV, receiving distance 18cm, micro pump push speed 1.08mL / h, receiving device speed 200r / min, perform electrospinning, deposit the nanofibers on the high-purity oxygen-free copper foil (50μm) of the collecting drum, control the spinning time to obtain a PAA nanofiber membrane with a thickness of 34μm; cut the PAA nanofiber membrane to a size of 6cm×6cm and put it into a tubular furnace and pass nitrogen for protection, and then heat it gradually: 40min to 80℃ for 1h; continue to heat from 80℃ to 160℃ for 40min for 1h; continue to heat from 160℃ to 250℃ for 45min for 1h; continue to heat from 250℃ to 350℃ for 50min for 0.5h; thermal imidization is performed under high temperature conditions to form a PI nanofiber membrane to obtain an electrode layer (Cu)-charge storage layer (PI) component;
[0150] The remaining steps and parameters are the same as those in Example 2.
[0151] Comparative Example 4
[0152] This comparative example provides a triboelectric nanogenerator and a preparation method thereof. Different from Example 2, in this comparative example, the preparation method of the triboelectric nanogenerator includes step S2 as follows:
[0153] S2. Preparation of charge storage layer-nanofiber membrane: load the PAA spinning solution into the electrospinning equipment, set the electrospinning process parameters as spinning voltage 26kV, receiving distance 18cm, micro pump push speed 1.08mL / h, receiving device speed 200r / min, perform electrospinning, deposit the nanofibers on the high-purity oxygen-free copper foil (50μm) of the collecting drum, control the spinning time to obtain a PAA nanofiber membrane with a thickness of 34μm; cut the PAA nanofiber membrane to a size of 6cm×6cm and put it into a tubular furnace and pass nitrogen for protection, and then heat it gradually: 40min to 80℃ for 1h; continue to heat from 80℃ to 160℃ for 40min for 1h; continue to heat from 160℃ to 250℃ for 45min for 1h; continue to heat from 250℃ to 350℃ for 50min for 0.5h; thermal imidization is performed under high temperature conditions to form a PI nanofiber membrane to obtain an electrode layer (Cu)-charge storage layer (PI) component;
[0154] The remaining steps and parameters are the same as those in Example 2.
[0155] Comparative Example 5
[0156] This comparative example provides a triboelectric nanogenerator and a preparation method thereof. Different from Example 2, in this comparative example, the preparation method of the triboelectric nanogenerator includes step S2 as follows:
[0157] S2. Preparation of charge storage layer - nanofiber membrane: load the PAA spinning solution into the electrospinning equipment, set the electrospinning process parameters as spinning voltage 20 kV, receiving distance 18 cm, micro pump push speed 0.36 mL / h, receiving device speed 200 r / min, perform electrospinning, deposit the nanofibers onto the high-purity oxygen-free copper foil (50 μm) on the collecting drum, control the spinning time to obtain a PAA nanofiber membrane with a thickness of 34 μm; cut the PAA nanofiber membrane into a size of 6 cm × 6 cm, put it into a tubular furnace and pass nitrogen for protection. The temperature was gradually increased from 40 min to 80°C for 1 h; then from 80°C to 160°C for 40 min for 1 h; then from 160°C to 250°C for 45 min for 1 h; then from 250°C to 350°C for 50 min for 0.5 h; the mixture was thermally imidized under high temperature to form a PI nanofiber membrane, thereby obtaining an electrode layer (Cu)-charge storage layer (PI) assembly;
[0158] The remaining steps and parameters are the same as those in Example 2.
[0159] Comparative Example 6
[0160] This comparative example provides a triboelectric nanogenerator and a preparation method thereof. Different from Example 2, in this comparative example, the preparation method of the triboelectric nanogenerator includes step S2 as follows:
[0161] S2. Preparation of charge storage layer-nanofiber membrane: load the PAA spinning solution into the electrospinning equipment, set the electrospinning process parameters as spinning voltage 20kV, receiving distance 18cm, micro pump push speed 1.80mL / h, receiving device speed 200r / min, perform electrospinning, deposit the nanofibers on the high-purity oxygen-free copper foil (50μm) of the collecting drum, control the spinning time to obtain a PAA nanofiber membrane with a thickness of 34μm; cut the PAA nanofiber membrane to a size of 6cm×6cm and put it into a tubular furnace and pass nitrogen for protection, and then heat it gradually: 40min to 80℃ for 1h; continue to heat from 80℃ to 160℃ for 40min for 1h; continue to heat from 160℃ to 250℃ for 45min for 1h; continue to heat from 250℃ to 350℃ for 50min for 0.5h; thermal imidization is performed under high temperature conditions to form a PI nanofiber membrane to obtain an electrode layer (Cu)-charge storage layer (PI) component;
[0162] The remaining steps and parameters are the same as those in Example 2.
[0163] Comparative Example 7
[0164] This comparative example provides a triboelectric nanogenerator and a preparation method thereof. Different from Example 2, in this comparative example, the preparation method of the triboelectric nanogenerator includes step S2 as follows:
[0165] S2. Preparation of charge storage layer-nanofiber membrane: load the PAA spinning solution into the electrospinning equipment, set the electrospinning process parameters as spinning voltage 20kV, receiving distance 18cm, micro pump push speed 1.08mL / h, receiving device speed 200r / min, perform electrospinning, deposit the nanofibers on the high-purity oxygen-free copper foil (50μm) of the collecting drum, control the spinning time to obtain a PAA nanofiber membrane with a thickness of 18μm; cut the PAA nanofiber membrane to a size of 6cm×6cm and put it into a tubular furnace and pass nitrogen for protection, and then heat it gradually: 40min to 80℃ for 1h; continue to heat from 80℃ to 160℃ for 40min for 1h; continue to heat from 160℃ to 250℃ for 45min for 1h; continue to heat from 250℃ to 350℃ for 50min for 0.5h; thermal imidization is performed under high temperature conditions to form a PI nanofiber membrane to obtain an electrode layer (Cu)-charge storage layer (PI) component;
[0166] The remaining steps and parameters are the same as those in Example 2.
[0167] Comparative Example 8
[0168] This comparative example provides a triboelectric nanogenerator and a preparation method thereof. Different from Example 2, in this comparative example, the preparation method of the triboelectric nanogenerator includes step S2 as follows:
[0169] S2. Preparation of charge storage layer - nanofiber membrane: The PAA spinning solution was loaded into the electrospinning equipment, and the electrospinning process parameters were set as spinning voltage 20 kV, receiving distance 18 cm, micro pump pushing speed 1.08 mL / h, and receiving device speed 200 r / min. Electrospinning was performed to deposit the nanofibers onto the high-purity oxygen-free copper foil (50 μm) of the collecting drum, and the spinning time was controlled to obtain a PAA nanofiber membrane with a thickness of 104 μm; the PAA nano The fiber membrane was cut into a size of 6 cm × 6 cm and placed in a tubular furnace and protected by nitrogen. The temperature was increased gradually: from 80°C for 40 minutes and kept for 1 hour; from 80°C to 160°C for 40 minutes and kept for 1 hour; from 160°C to 250°C for 45 minutes and kept for 1 hour; from 250°C to 350°C for 50 minutes and kept for 0.5 hours; the membrane was thermally imidized under high temperature conditions to form a PI nanofiber membrane, and an electrode layer (Cu)-charge storage layer (PI) component was obtained;
[0170] The remaining steps and parameters are the same as those in Example 2.
[0171] Comparative Example 9
[0172] This comparative example provides a triboelectric nanogenerator and a preparation method thereof. Different from Example 2, Kapton is used in this comparative example. ® Commercial polyimide film as the charge storage layer of triboelectric nanogenerator.
[0173] The preparation method of the triboelectric nanogenerator provided in this comparative example is:
[0174] Cut a piece of Kapton with a size of 6cm×6cm and a thickness of 25μm ® Commercial polyimide film, use conductive glue to bond the electrode layer (Cu) and the charge storage layer (commercial PI) to obtain the electrode layer (Cu)-charge storage layer (commercial PI) assembly; use conductive glue to bond the electrode layer (Cu)-charge storage layer (commercial PI) assembly to a transparent acrylic substrate, and connect the wire between the substrate and the copper electrode; select a PTFE film with a thickness of 25μm and cut it to a size of 6cm×6cm as a friction layer, and then use conductive glue to bond the PTFE film to one side of the commercial PI film to prepare TENG.
[0175] The triboelectric nanogenerators prepared in Examples 1-10 and Comparative Examples 1-9 were installed on a triboelectric performance test platform, and the parameters were set as follows: contact distance 4 mm, contact pressure 20 N, and contact frequency 2 Hz; a graphic sampling multimeter and a high resistance / low current electrometer were used to perform open circuit voltage, short circuit current, and transfer charge tests on the TENG.
[0176] Figure 2It is a working principle diagram of the embodiments 1, 2, 11 and 12 of the invention; wherein, Figure 2 (a) is the schematic diagram of the first working cycle of TENG. Figure 2 (b) is a schematic diagram of the subsequent working cycle of TENG, where I is the initial state of TENG; II is the contact state of TENG; III is the separation state of TENG; IV is the complete separation state of TENG; V is the contact state of TENG; the TENG described in Examples 1, 2, 11, and 12 is a single-electrode mode. Figure 2 As shown in (a), when in state I, the friction material and the electrode material have no contact, and there is no charge in the friction layer and the storage layer; when in state II, the friction material and the electrode material are in contact with each other. Due to the contact electrification effect, the friction material and the electrode material generate opposite charges respectively. At this time, there is no open circuit voltage and no charge flow; when in state III, the friction material and the electrode material are separated from each other, and a potential difference is generated between the electrode material and the grounding end of the electrode material. At this time, an open circuit voltage is generated. At the same time, the charge in the TENG will flow between the electrode material and the grounding end under the drive of the electric field force to form a current. At this time, part of the charge is stored in the charge storage layer; when in state IV, the separation distance between the electrode material and the friction material reaches the maximum value, the potential difference in the external circuit disappears, and the charge no longer flows; when in state V, the friction material and the electrode material approach each other again, and the potential difference between the electrode material and the grounding end gradually decreases. The charge will be driven by the electric field force to flow in the opposite direction to form a current until it reaches the contact state again, at which time a cycle of movement is completed. The subsequent working cycle is as follows Figure 2 As shown in (b), after the first working cycle, the charge storage layer in state I has stored part of the charge. In the subsequent contact separation, while the friction layer generates charge, the storage layer will also continuously store and release charge, which weakens the charge attenuation of the friction layer, improves its charge retention ability and surface charge density, and thus improves the output performance of TENG.
[0177] Figure 3 The fiber microstructure diagram of the nanofiber membrane prepared in Examples 2, 3, 4 and Comparative Examples 1 and 2 of the present invention; wherein, Figure 3 (a) corresponds to proportion 1, Figure 3 (b) corresponds to Example 3, Figure 3 (c) corresponds to Example 2, Figure 3 (d) corresponds to Example 4, Figure 3 (e) corresponds to ratio 2; Figure 3 It can be seen that the nanofiber membranes of Examples 2, 3, and 4 have better fiber morphology and more uniform distribution than those of Comparative Examples 1 and 2.
[0178] Figure 4The fiber diameter distribution diagram of the nanofiber membranes prepared in Examples 2, 3, 4 and Comparative Examples 1 and 2 of the present invention; wherein, Figure 4 (a) corresponds to proportion 1, Figure 4 (b) corresponds to Example 3, Figure 4 (c) corresponds to Example 2, Figure 4 (d) corresponds to Example 4, Figure 4 (e) corresponds to ratio 2; Figure 4 It can be seen that with the increase of concentration, the diameter of the obtained nanofibers increases significantly; the fiber diameters of comparative examples 1 and 2 are dispersedly distributed at 0.3-2.8 μm, and the fiber diameters of embodiments 2, 3, and 4 are concentratedly distributed at 0.4-0.8 μm. The nanofiber membranes of embodiments 2, 3, and 4 have better fiber formation and uniformity than those of comparative examples 1 and 2.
[0179] Figure 5 The open circuit voltage, short circuit current and transfer charge diagram of the triboelectric nanogenerator prepared in Examples 2, 3, 4 of the present invention and Comparative Examples 1 and 2; wherein Figure 5 (a) is the open circuit voltage diagram. Figure 5 (b) is the short-circuit current diagram. Figure 5 (c) is a transfer charge diagram, in which the red line corresponds to Example 1, the blue line corresponds to Example 3, the green line corresponds to Example 2, the purple line corresponds to Example 4, and the yellow line corresponds to Example 2; Figure 5 It can be seen that the triboelectric nanogenerators provided by Examples 2, 3, and 4 have larger open circuit voltage, short circuit current, and transferred charge than those of Comparative Examples 1 and 2, reaching up to 146 V, 3.47 μA, and 63 nC, respectively, proving that the triboelectric nanogenerators provided by Examples 2, 3, and 4 have better output performance.
[0180] Figure 6 The fiber microstructure diagram of the nanofiber membrane prepared in Examples 2, 5, 6 and Comparative Examples 3 and 4 of the present invention; wherein, Figure 6 (a) corresponds to proportion 3, Figure 6 (b) corresponds to Example 5, Figure 6 (c) corresponds to Example 2, Figure 6 (d) corresponds to Example 6, Figure 6 (e) corresponds to ratio 4; Figure 6 It can be seen that the nanofiber membranes provided by Examples 2, 5, and 6 have better fiber morphology and more uniform distribution than those of Comparative Examples 1 and 2.
[0181] Figure 7 Fiber diameter distribution diagram of the nanofiber membranes prepared in Examples 2, 5, 6 of the present invention and Comparative Examples 3 and 4; Figure 7 (a) corresponds to proportion 3, Figure 7 (b) corresponds to Example 5, Figure 7 (c) corresponds to Example 2, Figure 7 (d) corresponds to Example 6, Figure 7 (e) corresponds to ratio 4; Figure 7 It can be seen that with the increase of voltage, the diameter of the obtained nanofibers gradually becomes thinner; the fiber diameters of comparative examples 3 and 4 are dispersedly distributed at 0.1-2.0 μm, and the fiber diameters of comparative examples 2, 5, and 6 are concentratedly distributed at 0.2-0.6 μm. The fiber formation and uniformity of embodiments 2, 5, and 6 are better than those of comparative examples 3 and 4.
[0182] Figure 8 The open circuit voltage, short circuit current and transfer charge diagram of the triboelectric nanogenerator prepared in Examples 2, 5, 6 of the present invention and Comparative Examples 3 and 4; wherein Figure 8 (a) is the open circuit voltage diagram. Figure 8 (b) is the short-circuit current diagram. Figure 8 (c) is a transfer charge diagram, in which the red line corresponds to Example 3, the blue line corresponds to Example 5, the green line corresponds to Example 2, the purple line corresponds to Example 6, and the yellow line corresponds to Example 4; Figure 8 It can be seen that the triboelectric nanogenerators provided by Examples 2, 5 and 6 have larger open circuit voltage, short circuit current and transferred charge than those of Comparative Examples 3 and 4, reaching up to 167 V, 3.06 μA and 68 nC respectively, which proves that the triboelectric nanogenerators provided by Examples 2, 5 and 6 have better output performance.
[0183] Fig. 9 The open circuit voltage, short circuit current and transfer charge diagram of the triboelectric nanogenerator prepared in Examples 2, 7, 8 of the present invention and Comparative Examples 5 and 6; wherein Fig. 9 (a) is the open circuit voltage diagram. Fig. 9 (b) is the short-circuit current diagram. Fig. 9 (c) is a transfer charge diagram, in which the red line corresponds to Example 5, the blue line corresponds to Example 7, the green line corresponds to Example 2, the purple line corresponds to Example 8, and the yellow line corresponds to Example 6; Fig. 9 As shown, it can be seen that the triboelectric nanogenerators provided by Examples 2, 7, and 8 have larger open circuit voltage, short circuit current, and transferred charge than those of Comparative Examples 5 and 6, which can reach 153V, 2.76μA, and 58nC, proving that the triboelectric nanogenerators provided by Examples 2, 7, and 8 have better output performance.
[0184] Fig.10 The open circuit voltage, short circuit current and transfer charge diagram of the triboelectric nanogenerator prepared in Examples 2, 9, 10 of the present invention and Comparative Examples 7 and 8; wherein Fig.10 (a) is the open circuit voltage diagram. Fig.10 (b) is the short-circuit current diagram. Fig.10(c) is a transfer charge diagram, in which the red line corresponds to Example 7, the blue line corresponds to Example 2, the green line corresponds to Example 9, the purple line corresponds to Example 10, and the yellow line corresponds to Example 8; Figure 8 As shown, it can be seen that the triboelectric nanogenerators provided by Examples 2, 9, and 10 have larger open circuit voltage, short circuit current, and transfer charge than those of Comparative Examples 7 and 8, which can reach 147V, 2.88μA, and 54nC, proving that the triboelectric nanogenerators provided by Examples 2, 9, and 10 have better output performance.
[0185] Fig.11 The nanofiber membrane prepared in Example 2 of the present invention and the commercial film prepared in Comparative Example 9 are used as charge storage layers for the open circuit voltage, short circuit current and transfer charge diagram of TENG; wherein Fig.11 (a) is the open circuit voltage diagram. Fig.11 (b) is the short-circuit current diagram. Fig.11 (c) is a transfer charge diagram, in which the red line corresponds to Example 9 and the blue line corresponds to Example 2; Fig.11 As shown, it can be seen that the nanofiber membrane of Example 2 has a larger open circuit voltage, short circuit current, and transfer charge than the commercial film of Comparative Example 9, which can reach 149V, 2.67μA, and 60nC, and has better output performance.
[0186] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the enlightenment of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present invention and the claims, which all fall within the protection of the present invention.
Claims
1. A triboelectric nanogenerator, characterized in that: It includes an electrode layer, a charge storage layer and a friction layer, wherein the charge storage layer is located between the electrode layer and the friction layer; The charge storage layer is a polymer nanofiber film, and the polymer is selected from one or more of polyimide, polyvinylidene fluoride, polydimethylsiloxane, polystyrene, polyethylene terephthalate and nylon.
2. The triboelectric nanogenerator according to claim 1, characterized in that: The thickness of the charge storage layer is 32 μm-98 μm; And / or, the friction layer has a thickness of 25 μm-50 μm.
3. A method for preparing a triboelectric nanogenerator according to any one of claims 1 to 2, characterized in that: include: The polymer solution is prepared into a nanofiber membrane by electrospinning and collected on the electrode layer to obtain an electrode layer-charge storage layer assembly; Laminating the electrode layer-charge storage layer assembly to the friction layer to obtain a triboelectric nanogenerator; Among them, if a polyimide nanofiber membrane is prepared, before the electrode layer-charge storage layer assembly is attached to the friction layer, the electrode layer-charge storage layer assembly needs to be placed in a tubular furnace for a thermal imidization reaction.
4. The method for preparing the triboelectric nanogenerator according to claim 3, characterized in that: When the nanofiber membrane is a polyimide nanofiber membrane, the preparation method of the polymer solution comprises: completely dissolving 4,4'-aminodiphenylamine in a solvent A, then adding pyromellitic dianhydride to carry out polymerization reaction to obtain a polyamic acid polymer solution, wherein the solvent A is selected from dimethylformamide or dimethylacetamide; When the nanofiber membrane is a polyvinylidene fluoride nanofiber membrane, the preparation method of the polymer solution comprises: adding polyvinylidene fluoride to solvent B, heating to 45-65° C. and stirring until the polyvinylidene fluoride is completely dissolved in solvent B, to obtain a polyvinylidene fluoride polymer solution, wherein the solvent B is selected from dimethylformamide, acetone or dimethyl sulfoxide; When the nanofiber membrane is a polydimethylsiloxane nanofiber membrane, the preparation method of the polymer solution comprises: completely dissolving polydimethylsiloxane in a solvent C, adding a crosslinking agent, and stirring until the polydimethylsiloxane is completely dissolved in the solvent C to obtain a polydimethylsiloxane polymer solution, wherein the solvent C is selected from dimethylformamide, tetrahydrofuran or ethyl acetate, the crosslinking agent is tetraethyl orthosilicate, and the mass ratio of the crosslinking agent to the polydimethylsiloxane is 1: (10-20); When the nanofiber membrane is a polystyrene nanofiber membrane, the method for preparing the polymer solution comprises: completely dissolving polystyrene in a solvent D to obtain a polystyrene polymer solution, wherein the solvent D is selected from dimethylformamide or tetrahydrofuran; When the nanofiber membrane is a polyethylene terephthalate nanofiber membrane, the preparation method of the polymer solution comprises: adding polyethylene terephthalate to a solvent E, heating to 48-68° C. and stirring until the polyethylene terephthalate is completely dissolved in the solvent E, to obtain a polyethylene terephthalate polymer solution, wherein the solvent E is selected from hexafluoroisopropanol, trifluoroacetic acid or chloroform; When the nanofiber membrane is a nylon nanofiber membrane, the method for preparing the polymer solution comprises: completely dissolving nylon in a solvent F to obtain a nylon polymer solution, wherein the solvent F is selected from dimethylformamide, dichloromethane, formic acid or dimethyl sulfoxide.
5. The method for preparing the triboelectric nanogenerator according to claim 4, characterized in that: The polymer has a dielectric constant greater than 1.8 and is polar; And / or, the concentration of the polymer solution is 14wt%-18wt%.
6. The method for preparing the triboelectric nanogenerator according to claim 3, characterized in that: The electrospinning speed is 0.72-1.44 mL / h, the voltage is 16-25 kV, and the receiving distance is 15.5-20.5 cm.
7. The method for preparing a triboelectric nanogenerator according to claim 3, characterized in that: The electrode layer-charge storage layer assembly is placed in a tube furnace for thermal imidization reaction, the reaction temperature is 250-350° C., and the tube furnace is heated in a gradient heating manner.
8. The method for preparing a triboelectric nanogenerator according to claim 3, characterized in that: After the electrode layer-charge storage layer assembly is attached to the friction layer, a wire needs to be connected to the electrode layer to obtain a triboelectric nanogenerator.
9. An application of a triboelectric nanogenerator in energy harvesting and self-powered sensors, characterized in that: The triboelectric nanogenerator is the triboelectric nanogenerator described in any one of claims 1-2, or is prepared by the preparation method described in any one of claims 3-8.
Citation Information
Cited By
Curtain-coating thick-film resin anticorrosive paint and preparation method thereof
CN120842946A